A new Chinese “Diaspora Moment”? - V. V. Sukhomlinova (Vestnik MGIMO-Universiteta, 2022)
Book review: Review of the book by Shelly Chan. Diaspora’s Homeland: modern China in the age of global migration. Durham, Duke University Press, 2018. 281 p.